B03 Identification and characterisation of overexpression suppressors of mutant huntingtin toxicity. (16th November 2010) - Mason, R; Fearnley, N; Bishop, C; Möller, T; Giorgini, F
Abstract : Several genetic and chemical modifier screens have been performed in yeast models of Huntington's disease (HD) to identify deletion suppressors, deletion enhancers and chemical modifiers of mutant huntingtin (htt) toxicity. These screens have provided valuable insights into the cellular processes altered in HD and led to the identification of several promising therapeutic compounds, including inhibitors of kynurenine-3-monooxygenase (KMO). To complement these screens we have performed an overexpression suppressor screen in a yeast model of HD. Using a yeast model of HD we have screened murine cDNA libraries and identified 84 unique murine cDNAs capable of suppressing mutant htt toxicity when overexpressed in yeast. The suppressors encode proteins involved in a range of cellular processes altered in HD, including apoptosis, response to oxidative stress, protein folding, vesicle trafficking, autophagy and mitochondrial function. Several suppressors have also previously been implicated in neurodegeneration. To validate the suppressors we have stably overexpressed cDNAs selected from several functional groups in an inducible PC12 model of HD. The eight cDNA suppressors tested all significantly reduce the activation of caspase 3/7 observed on induction of mutant htt expression in this cell model. Three of these suppressors also improve several metrics in a Drosophila model of HD. In conclusion, we have identified a large number of suppressors of mutant htt toxicity and validated a number of these using a range of models. The validation of a subset of these suppressors in both mammalian and Drosophila models of HD suggests that the majority of the 84 cDNAs identified in the yeast screen will retest in higher organisms. This screen has identified several cellular pathways and specific proteins for therapeutic targeting and we are currently in the process of testing compounds that mimic overexpression of selected suppressors.